Empowering Surgeons, Anesthesiologists, and Obstetricians to Incorporate Environmental Sustainability in the Operating Room. Issue 6 (June 2021) - Yates, Elizabeth F.; Bowder, Alexis N.; Roa, Lina; Velin, Lotta; Goodman, Andrea S.; Nguyen, Louis L.; McClain, Craig D.; Meara, John G.; Cooper, Zara
Abstract : Objective: We review the existing research on environmentally sustainable surgical practices to enable SAO to advocate for improved environmental sustainability in operating rooms across the country. Summary of Background Data: Climate change refers to the impact of greenhouse gases emitted as a byproduct of human activities, trapped within our atmosphere and resulting in hotter and more variable climate patterns. 1 As of 2013, the US healthcare industry was responsible for 9.8% of the country's emissions 2 ; if it were itself a nation, US healthcare would rank 13th globally in emissions. 3 As one of the most energy-intensive and wasteful areas of the hospital, ORs drive this trend. ORs are 3 to 6 times more energy intensive than clinical wards. 4 Further, ORs and labor/delivery suites produce 50%–70% of waste across the hospital. 5, 6 Due to the adverse health impacts of climate change, the Lancet Climate Change Commission (2009) declared climate change "the biggest global health threat of the 21 st century" and predicted it would exacerbate existing health disparities for minority groups, children and low socioeconomic patients. 7 Methods/Results: We provide a comprehensive narrative review of published efforts to improve environmental sustainability in the OR while simultaneously achieving cost-savings, and highlight resources for clinicians interested in pursuing this work. Conclusion: Climate change adversely impacts patient health, and disproportionately impacts the most vulnerable patients. SAO contribute to the problem through their resource-intensive work in the OR and are uniquely positioned to lead efforts to improve the environmental sustainability of the OR.